Teaching case: Analysis of an electronic voting system - Thompson, Nik; Toohey, D. (Journal of Information Systems Education, 2014)
This teaching case discusses the analysis of an electronic voting system. The development of the case was motivated by research into information security and management, but as it includes procedural aspects, organizational structure and personnel, it is a suitable basis for all aspects of systems analysis, planning and design tasks. The material is based on real life analysis of currently used electronic voting systems, which have been generalized so as to highlight the wider issues and to not identify with any particular implementation of electronic voting. Suggested project deliverables are described in the teaching case, and these are complemented by the associated teaching notes which detail sample solutions and discussion points for class.